The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.pain.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in endogenous pain modulation by distracting and painful conditioning stimulation

Abstract: Sex differences in endogenous pain modulation were tested in healthy volunteers (32 men, 30 women). Painful contact heat stimuli were delivered to the right leg alone, and then in combination with various electrical conditioning stimuli delivered to the left forearm. Four conditioning protocols were applied to each subject in separate sessions: mild, nonpainful (control); distracting; stressfulyet-nonpainful; strongly painful. Thermal stimuli were rated on visual analog scales for pain intensity (INT) and unpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 62 publications
8
54
0
3
Order By: Relevance
“…[2,3,19,20] In our data is consistent with previous studies [2,3] and indicated greater pain levels among females compared with males.…”
Section: Discussionsupporting
confidence: 93%
“…[2,3,19,20] In our data is consistent with previous studies [2,3] and indicated greater pain levels among females compared with males.…”
Section: Discussionsupporting
confidence: 93%
“…Some epidemiological studies attribute this finding to an information bias 32 , however, it is plausible, since women, more and more, combine the execution of domestic tasks and jobs done out of home, where they are exposed to ergonomic loads, especially the repeatability, vicious positions and high velocity tasks' performance 33 . In addition, the female gender presents some anatomic functional characteristics (smaller stature, smaller muscle and bone masses, frail joints and less adapted to strenuous physical efforts as well as having a higher proportion of fat) 1,34,35 and others related to the nervous system which can collaborate to the emergence and increase of pain intensity 36,37 . The worst the health perception, the higher was the risk to have spinal pain (p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Psychosocial factors contribute substantially to pain perception in humans and may differentially influence pain in men and women [64,101,159,167,172]. There are welldocumented sex differences in stress responses in both animals and humans [112], and sex differences in mechanisms of stress-induced analgesia have been reported in rodents [141].…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, changes in spinal aromatase activity dramatically and immediately affected pain thresholds in the Japanese quail, without changes in plasma levels of gonadal steroids [56,57]. Future studies in which various steroidogenic enzyme inhibitors (or hormone agonists or antagonists) are locally infused would contribute to our understanding of how local changes in hormone action result in behavioral changes in sensitivity to pain and analgesia.How do psychological factors such as stress, mood, and conditioning (expectation) contribute to sex differences in pain/analgesia?Psychosocial factors contribute substantially to pain perception in humans and may differentially influence pain in men and women [64,101,159,167,172]. There are welldocumented sex differences in stress responses in both animals and humans [112], and sex differences in mechanisms of stress-induced analgesia have been reported in rodents [141].…”
mentioning
confidence: 99%